Antibodies Against Lysophosphatidic Acid Protect Against Blast-Induced Ocular Injuries - Arun, Peethambaran; Rossetti, Franco; DeMar, James C.; Wang, Ying; Batuure, Andrew B.; Wilder, Donna M.; Gist, Irene D.; Morris, Andrew J.; Sabbadini, Roger A.; Long, Joseph B. (Frontiers in Neurology, 2020)
Exposure to blast overpressure waves is implicated as the major cause of ocular injuries and resultant visual dysfunction in veterans involved in recent combat operations. No effective therapeutic strategies have been developed so far for blast-induced ocular dysfunction. Lysophosphatidic acid (LPA) is a bioactive phospholipid generated by activated platelets, astrocytes, choroidal plexus cells, and microglia and is reported to play major roles in stimulating inflammatory processes. The levels of LPA in the cerebrospinal fluid have been reported to increase acutely in patients with traumatic brain injury (TBI) as well as in a controlled cortical impact (CCI) TBI model in mice. In the present study, we have evaluated the efficacy of a single intravenous administration of a monoclonal LPA antibody (25 mg/kg) given at 1 h post-blast for protection against injuries to the retina and associated ocular dysfunctions. Our results show that a single 19 psi blast exposure significantly increased the levels of several species of LPA in blood plasma at 1 and 4 h post-blast. The anti-LPA antibody treatment significantly decreased glial cell activation and preserved neuronal cell morphology in the retina on day 8 after blast exposure. Optokinetic measurements indicated that anti-LPA antibody treatment significantly improved visual acuity in both eyes on days 2 and 6 post-blast exposure. Anti-LPA antibody treatment significantly increased rod photoreceptor and bipolar neuronal cell signaling in both eyes on day 7 post-blast exposure. These results suggest that blast exposure triggers release of LPAs, which play a major role promoting blast-induced ocular injuries, and that a single early administration of anti-LPA antibodies provides significant protection.